Pengaruh Pengiriman Paket Konstan dan Variabel di Lingkungan Wireless Mesh Network menggunakan Protokol Routing OLSR (Open Link-State Routing) - Riza Anisul Fu'ad; Dany Primanita Kartikasari; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
A wireless mesh network is a network,consisting of,a collection of wireless nodes that are connected to each other and then form a distributed network. Advantages of,wireless mesh network itself, namely in terms of flexibility, scalability and robustness, it is better than other conventional wireless networks. Characteristics Wireless mesh network It is also different from other ad hoc networks, which can be seen from the multi-hoop system, which can make connectivity capabilities in the network faster. In a plural environment, the connection is usually very constrained due to various factors such as trees, fog, and geographical conditions. In the research that has been done, the results show that the OLSR routing protocol has the best results for use on wireless mesh networks compared to other routing protocols on throughput and delay parameters. This research discusses the effect of constant and variable package delivery on a wireless mesh network using the OLSR routing protocol. The test scenario is carried out by changing the number of active nodes, namely 30, 25, 20, 15, 10, and 5, with QoS testing parameters including throughput, end-to-end delay, and packet loss. The best results of the throughput test were obtained from constant packet delivery in the scenario of 15 nodes with 206.43 kbps, which means it has a bad category, so there must be a limit on bandwidth to maintain the performance of the wireless mesh network. The best end-to-end delay test results were obtained for constant packet delivery in the five node scenario with 11867 ms, which means it has a bad category and will affect the performance of a wireless mesh network. The best test results for packet loss obtained from variable packet delivery in the scenario of 10 nodes were 63.466%, which means it has a bad category and affects the performance of the wireless mesh network because too much data is wasted.